Bioassays and coagulation studies using Moringa oleifera seeds for the removal of textile dyes - Pecora, Hengli Barbosa [UNESP]; Dilarri, Guilherme [UNESP]; Mendes, Carolina Rosai [UNESP]; Corso, Carlos Renato [UNESP] (IWA Publishing, 2018)
The aim of this work was to evaluate the removal of three different textile dyes through the coagulation action of the powder and supernatant of Moringa oleifera seeds. The pH of the solution and mass concentrations of the adsorbent were varied. Fourier transform infrared (FT-IR) spectrophotometry was used to evaluate the main interaction sites of the M. oleifera coagulants with the dyes. Bioassays were also conducted with Lactuca sativa and Eruca sativa seeds to evaluate the toxicity of the M. oleifera coagulants and dyes. Each dye interacted differently with the M. oleifera powder and supernatant; however, dye removal rates were higher than 70% even when varying the pH of the solution. FT-IR spectrophotometry revealed that the linkage of the dyes with the M. oleifera coagulants occurs through chemical interactions, and the coagulating protein of M. oleifera was confirmed as the removing agent. Depending on the dye molecule, the pH of the solution also exerted a strong influence on coagulation. The phytotoxicity tests showed that the coagulants in the seeds of M. oleifera are more toxic than the dyes tested. In conclusion, although efficient and economically feasible, the application of M. oleifera coagulants requires further investigation, especially with regard to ecotoxicology.
Keywords: Bioremediation; Chemisorption; Phytotoxicity test; Seeds; Toxicity test